2019
DOI: 10.1021/acs.jpcb.9b02227
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion and Trapping of Carbon Nanostructures in Nonisotropic Suspensions of Cellulose Nanostructures

Abstract: Incorporation of carbon nanotubes (CNTs) into liquid crystalline phases of cellulose nanocrystals (CNCs) may be used for preparation of hybrids with novel optical, electrical, and mechanical properties. Here, we investigated the effect of nanoparticle diameter, geometry, aspect ratio, and flexibility on the exclusion of dispersed carbon nanostructures (CNs) from the chiral nematic phase (N*) of the CNCs. Although the CNs are nicely dispersed in isotropic suspensions of CNCs, we observe that fullerenes, carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Yet, recent studies of hydrophobic particles of different size (from a few nanometers to hundreds of nanometers) and shape (spherical and elongated) indicate that carbonaceous inclusions are excluded from the N*, irrespective of their shape and size. This observation suggests that in the hybrid systems, hydrophobic interactions may play a more significant role than expected [12].…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Yet, recent studies of hydrophobic particles of different size (from a few nanometers to hundreds of nanometers) and shape (spherical and elongated) indicate that carbonaceous inclusions are excluded from the N*, irrespective of their shape and size. This observation suggests that in the hybrid systems, hydrophobic interactions may play a more significant role than expected [12].…”
Section: Introductionmentioning
confidence: 79%
“…Liquid suspensions of CNCs and SWNTs can be used as colloidal inks for additive manufacturing [51] and layer-by-layer deposition [18] of multifunctional nanocomposites with novel combinations of optical, electrical, mechanical, and thermal properties [18,[52][53][54]]. Yet, mismatch in the physical characteristics of the two components, including diameter, aspect ratio, rigidity, and interfacial interactions, results in segregation of the components and depletion of the SWNTs from the liquid-crystalline phases of the CNCs [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Confining anisotropic LC fluid into an emulsion system is widely explored as a LC emulsion and displays distinctive nano- and microstructures. When the prepared LC emulsion shows microscale droplet morphology, the LC orientational order can be frustrated in confined spherical geometries by the interplay between boundary conditions and energy minimization, yielding complex behaviors to control microscale colloidal self-assembly with super structures that are distinguished from the bulk phase. Interestingly, some colloidal particles can self-align along a common axis at high concentrations, resulting in the anisotropic LC phase with long-range ordered particle assembly. For example, cellulose nanocrystals (CNCs) are charged, rod-like nanoparticles that can self-assemble into a cholesteric LC phase above the critical concentration. The cholesteric organized CNC suspension is extremely stable with the presence of polymers, micro-/nanoparticles, and surfactants and can be further solidified into photonic films upon slow solvent evaporation. Several studies have shown that CNCs could be used as a robust LC building block for designing custom-tailored functional materials in the dry state; in contrast, few works have focused on the CNC colloidal self-assembly as LC emulsions. Owing to the nanoparticle stabilizing effect at the liquid–liquid interface, the aqueous CNC cholesteric phase can be confined directly within the suspended droplet (water-in-oil), in the inverted continuous phase (oil-in-water), or both phases (water-in-water), generating a immiscible LC-fluid interface with hierarchically ordered structures.…”
Section: Introductionmentioning
confidence: 99%